Enhancing cognitive engagement through movement: Investigating the impact of kinaesthetic learning activities on learners with intellectual disabilities in Lagos State - Kuku, Olaotan Oladele (CV. Yudhistt Fateeh, 2025)
Education remains the right of every child. However, learners with intellectual disabilities regularly encounter noteworthy challenges in accessing and benefiting from learning in conventional classroom settings. As a result, this study seeks to examine the impact of kinaesthetic learning activities on the cognitive engagement of students with intellectual disabilities in special needs schools across Lagos State, Nigeria. The study employed a quasi-experimental pre-test/post-test control group research design. The study involved 60 learners selected from two special schools in Lagos state using simple random and purposive sampling. An Observation Checklist was used to collect data on cognitive engagement. The data collected were analysed using descriptive statistics (such as mean, standard deviation, mean difference) and inferential statistics (analysis of covariance). The hypotheses were tested at 0.05 level of significance. The study revealed that learners who were engaged with kinaesthetic learning activities showed significantly higher levels of cognitive engagement compared to their counterpart taught with the conventional method. In addition, gender was observed to have no significant impact on the cognitive engagement of learners. Based on the findings, one of the recommendations given was that special need schools in Lagos State should incorporate kinaesthetic learning activities to enhance engagement and skill acquisition among students with intellectual disabilities.